LEVELS OF HIF1A IN THE BLOOD OF VOLUNTEERS UNDER CONDITIONS OF 100-DAY NORMOBARIC HYPOXIA (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The aim of the study was to evaluate the content of HIF1α in the blood of healthy male volunteers, considered as a marker of adaptation to long-term exposure to subthreshold (harmless) levels of normobaric hypoxic hypoxia. Under special bench conditions, the state of normobaric hypoxia was simulated for 100 days, changing the composition of the gaseous medium from 20 vol.% to 12 vol.%. Clinical blood counts and HIF1α levels were studied in dynamics by enzyme-linked immunosorbent assay in 6 test volunteers. Clinically significant RBC Response to prolonged exposure to a normobaric hypoxic breathing mixture did not significantly change the erythrocyte response in volunteers. During the adaptation period (the first 30 days), the level of HIF1α in the blood progressively decreased, then (from day 45) it began to recover, and in the period of 60-100 days did not differ from the initial values. HIF1α in the blood can be considered as a marker of adaptation to long-term exposure to hypoxia, as well as a marker of the preconditioning effects of hypoxia.
Keywords: normobaric hypoxia, adaptation, HIF1α, preconditioning markers.